Respecting, Protecting and Fulfilling the Human Right to Health - Nampewo, Zahara; Mike, Jennifer Heaven; Wolf, Jonathan (International Journal for Equity in Health, 2022)
Human rights are best protected, promoted and guaranteed when they can compel binding and enforceability duty. One prominent criticism of category of human rights which includes the human right to health is that it is difficult, to assign the duties that correspond to these rights, because of stark disparity in how the main duty bearers approach their duties. This paper adopts a doctrinal approach to examine and evaluate the duties to the right to health. The method in this study entails a detailed literature search to systematically evaluate the legal implications, regulations, arguments and policy regarding the nature of the obligation to the right to health. This study also engages with normative and philosophical aspects of human rights.
Keywords: Human right to health, Respect, Protect, Fulfl, Implementation